2022
DOI: 10.1063/5.0089745
|View full text |Cite
|
Sign up to set email alerts
|

Rotational excitation of NS+ by H2 revisited: A new global potential energy surface and rate coefficients

Abstract: Due to the lack of specific collisional data, the abundance of NS+ in cold dense interstellar clouds was determinedusing collisional rate coefficients of CS as substitute. To better understand the chemistry of sulfur in the interstellarmedium, further abundance modeling using the actual NS+ collisional rate coefficients are needed. For this purpose,we have computed the first full 4D potential energy surface of the NS+−H2 van der Waals complex using the explicitly correlated coupled cluster approach with single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
2
2
1
Order By: Relevance
“…In accordance with the results of previous authors, the cross sections we computed with the ortho-H 2 projectile are somewhat larger compared to the para-H 2 data, but the differences usually do not exceed 10%. It is worth noticing that for some transitions we observe more pronounced differences (up to about 20 − 30%) at higher energies (⩾ 400 cm −1 ), which is different from what was generally found for other ion + molecule collisions, where the main differences were present in the low-energy regime (see, for example, the works by Bop et al (2022) and Denis-Alpizar et al (2022)). This feature is most probably associated to the larger anisotropy of the PES with respect to H 2 rotation in the short range.…”
Section: Rotational De-excitation Cross Sectionscontrasting
confidence: 99%
See 1 more Smart Citation
“…In accordance with the results of previous authors, the cross sections we computed with the ortho-H 2 projectile are somewhat larger compared to the para-H 2 data, but the differences usually do not exceed 10%. It is worth noticing that for some transitions we observe more pronounced differences (up to about 20 − 30%) at higher energies (⩾ 400 cm −1 ), which is different from what was generally found for other ion + molecule collisions, where the main differences were present in the low-energy regime (see, for example, the works by Bop et al (2022) and Denis-Alpizar et al (2022)). This feature is most probably associated to the larger anisotropy of the PES with respect to H 2 rotation in the short range.…”
Section: Rotational De-excitation Cross Sectionscontrasting
confidence: 99%
“…Our further important finding following the analysis of cross sections is that the data obtained for the 𝑝−H 2 and 𝑜−H 2 projectiles are very similar. This is an expected behaviour, and the same tendency was observed earlier for several other 'ion + molecular hydrogen' collision schemes, for example recently for NS + + H 2 (Bop et al 2022) (Kłos & Lique 2011). According to Lara-Moreno et al (2019) these similarities between the 𝑝−H 2 and 𝑜−H 2 cross sections could be attributed to the features of the short-range interaction of the colliders, which gives relevant contributions in the coupling matrix elements equally for 𝑝−H 2 and 𝑜−H 2 .…”
Section: Rotational De-excitation Cross Sectionssupporting
confidence: 88%
“…This highlights that, for this system, the use of a 2D-PES obtained by an average over three H 2 orientations does not allow to obtain results with an accuracy better than 30%. Bop et al 29 obtain a similar conclusion in the study of rotational excitation of NS + by para-H 2 . This shows the need for using a PES describing all orientations of H 2 in cases where the PES exhibits large anisotropies at R-distances dominant for the nuclear dynamics.…”
Section: Please Cite This Article Assupporting
confidence: 61%
“…28 However, because of the strong anisotropy of the interaction PES with respect to the orientation of H 2 usually found for ionic species, the use of a reduced dimension PES could lead to inaccuracies in the determination of para-H 2 rate coefficients, as found recently for NS + -H 2 collisions. 29 Moreover, calculations with a 2D-PES do not allow to obtain the data for collisions with ortho-H 2 , much needed for the non-LTE modeling of media where both para-and ortho-H 2 are considered important colliders.…”
Section: Introductionmentioning
confidence: 99%
“…The de-excitation among rotational levels of NS + cation by H 2 has been included with several datasets: a first dataset (Bop 2019; 24 levels; T = 5-100 K) of NS + in collision with p-H 2 ( j = 0) that was calculated with a PES spherically averaged over the H 2 directions, and two datasets (Bop et al 2022a; 15 levels; T = 5-50 K) in collision with p-H 2 ( j = 0) and with o-H 2 ( j = 1); both datasets were calculated with a 4D PES (Bop et al 2022a). For these datasets, the authors (Bop et al 2022a) performed some interesting precision tests related to the dimension of the H 2 rotational basis in the dynamical calculations. They found that the neglect of higher H 2 rotational levels induced differences up to 30% in the rate coefficients.…”
Section: Anions and Cationsmentioning
confidence: 99%

BASECOL2023 scientific content

Dubernet,
Boursier,
Denis-Alpizar
et al. 2024
A&A
Self Cite